Pengembangan Sayuran Lokal dengan Vertikultur pada Pekarangan Keluarga (Family Farming) - Catur Wasonowati (LPPM Universitas Trunojoyo Madura, 2021)
Indonesia is a country that has abundant biodiversity including local vegetable crops that have long been consumed by the Indonesian people, so it was necessary to increase productivity, production, and quality with various innovations that are cheap and easy to apply. Verticulture is an agricultural cultivation system that was carried out vertically or stratified and a technique of cultivating vegetables on limited land which was arranged in layers with a particular container model by applying advanced technology packages and high economic value commodities. This verticulture can be applied in the Family Farming. This family farming program will affect food security and fulfillment of nutrition for each family. Abdimas activities was carried out in Socah Village, Socah District, Bangkalan Regency, consisting of the introduction and training of the local vegetable crop verticulture method as well as assistance in the use of family farming and narrow land for housewives or the community so that later it can improve the ability of housewives or the community economically and socially in meeting the nutritional needs of families and communities.